Looking at the effect of TaRL-integrated CBL on students' scientific literacy skills: What we can learn? - Annisa Ibrahim; Ervan Johan Wicaksana; Fitri Astriawati (International Journal on Education Insight, 2025)
In the 21st century, scientific literacy is essential for students to face the complexity of global problems that require scientific understanding in decision-making. PISA data shows Indonesia's low scientific literacy. In 2018, it ranked 74th out of 79 countries with a score of 396 (40% of students only reached level 1), and in 2022, it dropped to 69th out of 81 countries with a score of 383 (34% of students at the elementary level). Less than 1% of Indonesian students reached levels 5-6 in both periods. Efforts to optimize scientific literacy were carried out by implementing a case-based learning (CBL) model integrated with the teaching at the right level (TaRL) approach. A quasi-experimental study was conducted at SMAN 1 Kota Jambi with the topic of the immune system using a non-randomized pretest-posttest control group design. The sample was selected using purposive sampling in grade XI, consisting of an experimental class (CBL-TaRL, n=36) and a control class (CBL, n=36). The results showed that the average score of the experimental class increased from 54.17 to 85.28, while the control class increased from 50.69 to 68.61. The one-way ANCOVA test showed a significant difference [F(1,69)=27.560, p<0.001, ηp²=0.28] with a large effect size. Students taught using CBL-TaRL had a higher increase in scientific literacy, especially in the aspects of analyzing scientific phenomena (36%) and designing scientific investigations (34%).